PENDEKATAN HUMANISTIK DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM PADA KMA 183 TAHUN 2019 - Ilham Putri Handayani; Tasman Hamami (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2022)
PAI has faced various problems and challenges in its learning process. PAI education learning is still traditional with a linear interaction pattern and the teacher is more dominant, so that students are passive. This learning process cannot develop all aspects of the individual potential of students as a whole. This problem stems from the design of the PAI curriculum which does not pay attention to holistic individual development. To overcome this problem, the Ministry of Religion developed a madrasa religious education curriculum as outlined in Minister of Religion Decree (KMA) number 183 of 2019. Curriculum development uses various approaches, including humanistic ones. The purpose of this study is to analyze and elaborate on the humanistic approach in developing the PAI curriculum in the Decree of the Minister of Religion (KMA) 183 of 2019. This article is based on literature research that uses content analysis to reveal a humanistic approach in the development of PAI curriculum. This research shows that the development of PAI curriculum in KMA 183 Year 2019 uses a humanistic approach and various other approaches. The humanistic approach in developing PAI curriculum provides a new perspective on PAI learning, characteristics of ideal teachers, as well as the development of evaluations, methods and learning media.